El espacio del esclavo negro en las haciendas del valle de Cañete, 1747-1821 - Morales Polar, Maria Angela (2008)
This paper interprets the consumption of the spaces in the haciendas of the Valley of Cañete by the black slaves in the period 1747-1821. The exploitation and control they were putted under due to their situation and the precarious conditions of the lives and spaces they were confined to, originates different answers of resistance and adaptation, in consequence of the necessity of survival. These answers consisted in their means of expression, in the spaces of the hacienda and the beginning of the creation of their culture, in the new territory.